Indonesia’s PPHAM Team and The Ghost of Impunity: Can Non-Judicial Reconciliation Succeed Without Confronting Perpetrators? - Arizona, Yance; Adli Wafi, Mochamad; Ananditha Bilal, Nasywa; Kouwagam, Santy (Jambe Law Journal, 2026)
Impunity for past gross human rights violations remains a structural feature of Indonesia’s legal-political order. After the Constitutional Court invalidated the 2004 Truth and Reconciliation Commission Law and the Ad Hoc Human Rights Courts repeatedly failed to convict perpetrators, the Joko Widodo administration established the Non-Judicial Settlement Team for Past Gross Human Rights Violations (PPHAM Team) through Presidential Decree 17/2022. This article applies a socio-legal approach to reconstruct the Team’s design and trace its post-Jokowi trajectory, drawing on two in-depth interviews with PPHAM Implementation Team members in 2024 and five focus group discussions and in-depth interviews with civil society organisations, Komnas HAM, the Ministry of Human Rights, and the Komnas HAM Papua Representative Office conducted between October and December 2025. Three contributions follow. First, the Implementation Team achieved a paradigm shift from charity-based to rights-based reparation. Second, the Attorney General’s Office–Komnas HAM deadlock under Law No. 26/2000 is the immediate institutional cause of PPHAM’s creation. Third, under President Prabowo Subianto the scheme has become operationally dormant, with PPHAM coordination administratively reassigned to the Coordinating Ministry for Politics and Security, re-classifying the work as a politico-security matter and eroding the rights-based paradigm. The article proposes integrated reform of Law No. 26/2000 alongside a permanent statutory reparation institution.